IMPLEMENTATION OF MIT APP INVENTOR IN GO REMPAH DEVELOPMENT - Rahayu Amalia; Rasmila; Chairullah; Yusriah Herawati (Jurnal Teknik Informatika (Jutif), 2022)
Spices are one of the raw materials needed for basic ingredients for food, beverages and medicines, of which the State of Indonesia is one of the spice producers who is ranked first in the world. Spices can be found in Traditional Markets and Modern Markets, however, there has been a drastic decline in spice buyers in Traditional Markets during the current Covid-19 pandemic. This has an impact on one of the traditional markets in the city of Palembang, namely "Pasar Km 5" so that it affects the income or economy of spice sellers. Therefore, in this research, a solution is designed that can be used to solve problems that occur by utilizing digital media that can be operated online. By using the Rapid Application Development (RAD) method, the researcher applies the MIT App Inventor to the android application development process which aims to introduce types of spices and as a marketing medium for spices. The RAD method has several stages, namely Requirements Planning, User Design (Prototype, Test, Refine), Construction and Cutover. This android application will be applied to the "Km 5 Market" to test its usefulness to suit the purpose of being a solution to the problem of spice sellers. After that, this android application will be used for several other traditional markets in Indonesia so that this android application is can named "Go Rempah" which will be a source of information and marketing of spices originating from Indonesia.